Dieu créateur, Seigneur du ciel et de la terre, dans le livre des Actes - Siffer, Nathalie (Revue des sciences religieuses, 2025)
By examining the fundamental elements of his conception of God, we can see that Luke comes to superimpose creative act and sovereign action. This contribution will seek to determine how he expresses the lordship of the Creator, or more precisely how the representation of God the Creator is linked to the expression of his sovereignty. Four passages from the book of Acts will be studied from this angle, each of which, in its own way, displaying the image of a God manifesting his lordship in and over his creation: Acts 4:24 ; 7:49-50 ; 14:15 ; 17:24. These statements also bear witness to a veritable network, sublimating this God who reveals himself to be both artisan and master of the creation, while placing it within the history of salvation that he himself initiated.